Adoption of Fodder Production and Conservation Technology in Bundelkhand, Uttar Pradesh, India - Narain, Sarju; Gupta, Shobhana; Rawat, Sudhir K (International Journal of Bio-resource and Stress Management, 2023)
Livestock keeping provides an assured income to the farmers of Bundelkhand region as it is more reliable than crop husbandry. The study was conducted in five districts of Bundelkhand region of Uttar Pradesh (India) in 2014-15. Total 200 respondents were interviewed. Respondents had highest knowledge about the item names of leguminous and non-leguminous roughages. It was ranked first followed by fodder requirement and cropping scheme preparation based on number of animals, and importance of different roughages for animal health was ranked third. The highest adoption was found for the practices for which respondents had highest knowledge. The highest constraints were related to technology transfer (83.85%) followed by constraints related to farmers purchasing capacity (63%) and some unavoidable factors (58.1%). Thus by addressing the issues of knowledge, adoption and constraints, the fodder production in the region can be enhanced and the farmers will get another assured source of income from livestock keeping.